A hitherto unknown river type from the Archaean at Bhurkuli (Jharkhand, E India) - Loon, A.J. (Tom) van; De, Shuvabrata (Geologos, 2017)
The Archaean granitoid pluton of the Singhbhum craton in E India is overlain by Archaean to Palaeoproterozoic metasediments. These sediments are still poorly known and their stratigraphy is under debate. Several scattered, most probably Meso- to Neoarchaean, conglomerates are present in the state of Jharkhand that differ so much in characteristics that they are probably not related to each other. The sedimentology of a series of conglomerate patches and layers near Bhurkuli has been investigated, including the characteristics of the clasts. It is deduced on the basis of these characteristics and the sedimentological context that the Bhurkuli conglomerates represent the channel facies of a river system that differed from the types of fluvial systems that exist nowadays.